Embodied reading in a transparent orthography. (August 2019) - Adams, Ashley Marie; Glenberg, Arthur M.; Restrepo, M. Adelaida
Abstract: The embodiment framework posits that reading comprehension requires simulation. That is, the reader must use perceptual, action, and emotional systems to create an analogical representation of the situation described in the text. Moved by Reading teaches children to simulate by having them a) move images on a computer screen to correspond to sentences (externalizing the simulation), and then b) imagine moving the images (internal simulation). Although Moved by Reading greatly enhances comprehension, it does not always produce transfer when children read new texts without manipulation. The decoding hypothesis provides an explanation: Before children can simulate the sentences, they must be able to decode the words. In orthographically opaque languages such as English, decoding skill greatly varies across children, hence limiting transfer when reading unfamiliar texts. If true, Moved by Reading should produce successful transfer in Spanish, an orthographically transparent language in which decoding is more transparent. As predicted, monolingual Spanish-speaking children taught simulation performed better than children in a control condition on comprehension tests a) for texts in which they moved images, b) for texts in which they imagined moving images, and c) most importantly, in an untrained transfer text. Thus, the data demonstrate the effectiveness of Moved by Reading in Spanish in line with predictions from the decoding hypothesis, and the results highlight a need for studies that directly compare the effects of this training across readers with different decoding skills and languages. Highlights: Spanish-speaking children used an embodied reading comprehension strategy. Comprehension improved (relative to a control) when physically manipulating images. Comprehension improved when imagining manipulation. Importantly, comprehension also improved in a transfer task.